2018
DOI: 10.1021/acs.orglett.8b02422
|View full text |Cite
|
Sign up to set email alerts
|

Development and Utilization of a Palladium-Catalyzed Dehydration of Primary Amides To Form Nitriles

Abstract: A palladium(II) catalyst, in the presence of Selectfluor, enables the efficient and chemoselective transformation of primary amides into nitriles. The amides can be attached to aromatic rings, heteroaromatic rings, or aliphatic side chains, and the reactions tolerate steric bulk and electronic modification. Dehydration of a peptaibol containing three glutamine groups afforded structure–activity relationships for each glutamine residue. Thus, this dehydration can act similarly to an alanine scan for glutamines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 59 publications
2
27
0
1
Order By: Relevance
“…Palladium-catalyzed dehydration of amides using acetonitrile as a dehydrating agent is known for its chemo-selectivity and compatibility over many other functionalities. 54,61,70 In 2005, Maffioli et al reported for the first time PdCl 2 catalysed reversible conversion of primary amides to nitriles in aqueous acetonitrile solvent (Scheme 20). 61,70 The dehydration of primary amides involved "water transfer" from the amide to acetonitrile.…”
Section: Metal Catalysed Dehydration Using Acetonitrile As a Dehydrating Agentmentioning
confidence: 99%
“…Palladium-catalyzed dehydration of amides using acetonitrile as a dehydrating agent is known for its chemo-selectivity and compatibility over many other functionalities. 54,61,70 In 2005, Maffioli et al reported for the first time PdCl 2 catalysed reversible conversion of primary amides to nitriles in aqueous acetonitrile solvent (Scheme 20). 61,70 The dehydration of primary amides involved "water transfer" from the amide to acetonitrile.…”
Section: Metal Catalysed Dehydration Using Acetonitrile As a Dehydrating Agentmentioning
confidence: 99%
“…A goal of the current study was to leverage our experience in natural products chemistry with expertise in synthetic chemistry [ 21 , 26 28 ]. Building from our knowledge of mycology and fungal metabolites, we strove to develop methods to generate the RALs on a scale that facilitates synthetic chemistry efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group reported mild conditions for the dehydration of primary amides using anhydrous acetonitrile (Scheme ) . In this method, Selectfluor (20 mol%) was used as an oxidant in the presence of catalytic amounts of PdCl 2 (10 mol%) and acetonitrile, which is essential for the dehydration of the amides.…”
Section: Metal‐catalyzed Dehydration Of Primary Amidesmentioning
confidence: 99%
“…The reaction time was optimized to enable the isolation of all cyano‐peptaibol derivatives ( 3 – 9 ) which were individually tested against three cancer cell lines. The activity of these cyano‐derivatives determined that Gln‐7 is important to maintain the activity of the parent compound . Thus, site specific molecular mutation using amide dehydration allowed for the facile determination of structure‐activity relationship of the glutamine residues of this peptaibol.…”
Section: Metal‐catalyzed Dehydration Of Primary Amidesmentioning
confidence: 99%